Northeast Historic Film and the Documentation of Maine’s History - Henderson, Jim; Sheldon, Karan (Maine Policy Review, 2015)
Moving images are among the most important documents of twentieth-century life as they capture policy steps taken and not taken, infrastructure created and abandoned, politicians’ campaigns and public governance, citizens’ work lives, social and cultural attitudes, industries, natural resources and their use. The authors reflect on the work of Northeast Historic Film and how it documents Maine history.